How Flexible are Treatments for Youth Internalizing Disorders? Examining Modification Guidelines Included across Supported Treatments. Issue 5 (3rd September 2022) - Georgiadis, Christopher; Bose, Deepika; Wolenski, Rebecca; Javadi, Natalie; Coxe, Stefany; Pettit, Jeremy W.; Comer, Jonathan S.
ABSTRACT: Objective: Treatment protocols for youth-internalizing disorders have been developed, however these protocols have yielded mixed findings in routine care settings. Despite increased recognition of the importance of flexibility when delivering evidence-based treatments (EBTs), little is known about the extent to which protocols offer guidance to providers in flexible EBT implementation. The current study examined the extent to which supported EBTs for youth internalizing disorders explicitly incorporate guidance for treatment modification. Methods: Supported treatment protocols for youth internalizing disorders were identified (N = 44), from which 4, 021 modification guidelines were extracted and coded using a structured coding system to classify modification strategies (i.e., the forms that recommended modifications take), and associated tailoring factors (i.e., the rationale for which modifications are recommended). Results: Across all EBTs, modification guidelines were quite common, with the average protocol including almost 91 text passages providing guidance for modification. The majority of modification guidelines functionally increase session or treatment length by recommending the addition or repetition of material, whereas less than 5% of modification guidelines provided strategies for condensing or streamlining care. Strikingly, less than 2% of modification guidelines in EBT protocols address patient cultural factors, and rarely address provider or setting issues that can challenge standard implementation. Conclusions: Findings highlight critical gaps in the available guidance to modify EBTs for youth internalizing disorders, and suggest EBT protocols may not be optimally poised to flexibly address the broad diversity of children and adolescents across varied settings in need of mental health care.